PENERAPAN PENDEKATAN SAINTIFIK BERBASIS MASALAH KONTEKSTUAL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK - Putik Rustika (Integral : Pendidikan Matematika, 2018)
This study aims to determine the differences in increasing the ability ofmathematical representation and the acquisition of mathematical problem solvingabilities between students who get learning with a scientific approach based oncontextual problems with students who get expository learning. This type ofresearch is quasi-experimental. The sample was 79 VII grade students who camefrom two classes in one State Junior High School in Lembang Regency. First classgets learning with a scientific approach based on contextual problems and thesecond class gets Expository learning. Both classes posttest mathematical problemsolving abilities. The results showed that (1) there was a difference in the overallacquisition of mathematical problem solving abilities between students whostudied with a scientific approach based on contextual problems and students whoreceived expository learning; (2) there are differences in the acquisition ofmathematical problem solving abilities based on students' initial mathematicalabilities (high, medium, low) (3) there is an influence of interaction between thelearning model and students' initial mathematical abilities on improving students'mathematical problem solving abilities. Keywords: Learning Scientific Approach Based on Contextual Problems,Mathematical Problem Solving